Serotype 19A and 6C Account for One-Third of Pneumococcal Carriage Among Belgian Day-Care Children Four Years After a Shift to a Lower-Valent PCV. Issue 1 (20th December 2022) - Ekinci, Esra; Van Heirstraeten, Liesbet; Willen, Laura; Desmet, Stefanie; Wouters, Ine; Vermeulen, Helene; Lammens, Christine; Goossens, Herman; Van Damme, Pierre; Verhaegen, Jan; Beutels, Philippe; Theeten, Heidi; et al.
Abstract: Background: Pneumococcal conjugate vaccines (PCVs) effectively reduce infection and asymptomatic carriage of Streptococcus pneumoniae vaccine serotypes. In 2016, Belgium replaced its infant PCV13 program by a 4-year period of PCV10. Concomitantly, S. pneumoniae serotype carriage was monitored together with the carriage of other nasopharyngeal pathogens in children attending day-care centers. Methods: From 2016 to 2019, a total of 3459 nasopharyngeal swabs were obtained from children aged 6–30 months. Culture and qPCR were used for the identification of S. pneumoniae, Haemophilus influenzae, Moraxella catarrhalis, and Staphylococcus aureus and for serotyping and antimicrobial susceptibility assessment of S. pneumoniae strains. Results: S. pneumoniae colonization was frequent and stable over the study years. H. influenzae and M. catarrhalis were more frequently carried ( P  < .001) than S. pneumoniae, by, respectively, 92.3% and 91.0% of children. Prevalence of all PCV13 serotypes together increased significantly over time from 5.8% to 19.6% ( P  < .001) and was attributable to the increasing prevalence of serotype 19A. Coincidently, non-vaccine serotype 6C increased ( P  < .001) and the overall pneumococcal non-susceptibility to tetracycline and erythromycin. Non-susceptibility to cotrimoxazole decreased ( P  < .001). Conclusions: The switch to a PCV program no longer covering serotypes 19A, 6A, and 3 was associated with a sustained increase of serotypes 19A and 6C in healthy children, similarly as in invasive pneumococcal disease. This resulted in a re-introduction of the 13-valent conjugate vaccine during the summer of 2019.